2012
DOI: 10.1371/journal.pone.0046390
|View full text |Cite
|
Sign up to set email alerts
|

Type-IVC Secretion System: A Novel Subclass of Type IV Secretion System (T4SS) Common Existing in Gram-Positive Genus Streptococcus

Abstract: A growing number of pathogens are being found to possess specialized secretion systems which they use in various ways to subvert host defenses. Type IV secretion system (T4SS) is one of versatile secretion systems essential for the virulence and even survival of some bacteria species, and they enable the secretion of protein and DNA substrates across the cell envelope. T4SS was once believed to be present only in Gram-negative bacteria. In this study, we present evidence of a new subclass of T4SS, Type-IVC sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 32 publications
0
53
0
3
Order By: Relevance
“…For conjugation systems in Gram-negative bacteria, structural resolution of the outer membrane core complex and the inner membrane complex of the T4SS, as well as information about the pathway of DNA translocation across the T4SS in the donor cell, has been elucidated (3)(4)(5)(6)(7)(8)(9)(10)(11). Less is known about conjugation systems in Gram-positive bacteria, with our current understanding based primarily on comparisons to those in Gramnegative bacteria and with the systems in Gram-positive bacteria proposed to involve a "minimized" T4SS (3,(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…For conjugation systems in Gram-negative bacteria, structural resolution of the outer membrane core complex and the inner membrane complex of the T4SS, as well as information about the pathway of DNA translocation across the T4SS in the donor cell, has been elucidated (3)(4)(5)(6)(7)(8)(9)(10)(11). Less is known about conjugation systems in Gram-positive bacteria, with our current understanding based primarily on comparisons to those in Gramnegative bacteria and with the systems in Gram-positive bacteria proposed to involve a "minimized" T4SS (3,(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…As three core genes of T4SS subtype, VirB4, VirB6 and VirD4 serve synergistic effects mediating DNA transfer (17). In a previous study, similar T4SS subtypes were detected in Streptococcus agalactiae, Streptococcus pneumonia and Pyogenic streptococcus (5). In addition, our study group first identified the existence of T4SS in C. difficile and its association with C. difficile virulence (5), suggesting that T4SS may serve as the vital mechanism underlying the secretion of toxins A and B.…”
Section: Discussionmentioning
confidence: 54%
“…2A, ORFs 1 to 19) in the predicted T4SS genetic locus of B. bifidum MIMBb75. These putative genes include the minimal components of the secretory system in Gram-positive bacteria (VirB1-, VirB4-, VirB6-, and VirD4-like proteins) and the proteins needed to support the conjugative transfer of DNA (37,38). Specifically, we found in MIMBb75 seven genes whose products contain conserved domains associated to vir molecular components of the Agrobacterium tumefaciens T4SS ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…The gene nomenclature of the 43-kbp Agrobacterium vir T4SS region has been used to refer also to T4SSs identified in Gram-positive bacteria (37,38).…”
Section: Resultsmentioning
confidence: 99%